2010 39th International Conference on Parallel Processing 2010
DOI: 10.1109/icpp.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Ring Networks: A Polymorphic Topology for Network-on-Chip

Abstract: Abstract-As chip multiprocessors transition from multi-core to many-core, on-chip network power is increasingly becoming a key barrier to scalability. Studies have shown that on-chip networks can consume up to 36% of the total chip power, while analysis of network traffic reveals that for extended periods of execution time, network load is well below the network capacity in many applications. In recent studies, researchers have proposed to exploit this temporal variability in network traffic to dynamically tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Many prior works have investigated techniques to save dynamic and static power of links [14,27,29]. These techniques can readily be used together with NoRD to provide more energy-efficient NoC designs.…”
Section: Related Workmentioning
confidence: 99%
“…Many prior works have investigated techniques to save dynamic and static power of links [14,27,29]. These techniques can readily be used together with NoRD to provide more energy-efficient NoC designs.…”
Section: Related Workmentioning
confidence: 99%
“…Cho et al [21] suggested adaptively adjusting the direction for each channel to improve the network throughput. By combining ring and mesh networks, Zafar et al [148] proposed the cubic ring topology, which supports dynamically shutting off 30% of routers to reduce power consumption. Compared with a baseline design, their design achieves similar performance with half of the channel resources.…”
Section: Research On Topologiesmentioning
confidence: 99%